2012
DOI: 10.1021/jm300335n
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of the First Dual Tyrosyl-DNA Phosphodiesterase I (Tdp1)–Topoisomerase I (Top1) Inhibitors

Abstract: Substances with dual tyrosyl-DNA phosphodiesterase I - topoisomerase I inhibitory activity in one low molecular weight compound would constitute a unique class of anticancer agents that could potentially have significant advantages over drugs that work against the individual enzymes. The present study demonstrates the successful synthesis and evaluation of the first dual Top1-Tdp1 inhibitors, which are based on the indenoisoquinoline chemotype. One bis(indenoisoquinoline) had significant activity against human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
95
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 48 publications
2
95
0
Order By: Relevance
“…29 Recently, a subset of indenoisoquinoline derivatives-Top1/Tdp1 dual inhibitors was discovered. 22 One bis(indenoisoquinoline) had significant activity against human Tdp1 (IC 50 = 1.52 ± 0.05 lM). At the same time and the same team had found out the more potent submicromolar inhibitor of Tdp1 arylidene thioxothiazolidinone (IC 50 = 0.87 lM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Recently, a subset of indenoisoquinoline derivatives-Top1/Tdp1 dual inhibitors was discovered. 22 One bis(indenoisoquinoline) had significant activity against human Tdp1 (IC 50 = 1.52 ± 0.05 lM). At the same time and the same team had found out the more potent submicromolar inhibitor of Tdp1 arylidene thioxothiazolidinone (IC 50 = 0.87 lM).…”
Section: Introductionmentioning
confidence: 99%
“…A few TDP1 inhibitors reported in the literature have relatively modest efficacy, that is, IC 50 values in the 1-100 lM range. 4,14,[21][22][23][24][25][26] First Tdp1 inhibitors discovered inhibit Tdp1 at millimolar range, including aminoglycoside antibiotics and the ribosome inhibitors, 27 as well as tungstates and vanadates which present mimetics of transition state substrate. 26,28 After that, a few micromolar inhibitors-phosphotyrosine mimetics were identified (for rev.…”
Section: Introductionmentioning
confidence: 99%
“…11 Recently, Cushman and co-workers reported that a subset of indenoisoquinoline derivatives potently inhibit both Top1 and Tdp1, making them the first Top1/Tdp1 dual inhibitors. 27 Nevertheless, though inhibiting Tdp1 at micromolar concentrations, these compounds remain far from therapeutic development. Therefore, there is a need to continue to identify potent and specific small molecule inhibitors to further advance the understanding of Tdp1 functions and develop therapeutic candidates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Because many cancer cell types have an already compromised capacity for DNA repair, inhibition of TDP1 and/or TDP2 may selectively reduce the ability of cancer cells to overcome the cytotoxic effects of Top1 poisons, and triple Top1/TDP1/TDP2 inhibitors would therefore be especially interesting. 16 A limited number of indenoisoquinolines, such as dimer 7 , 17 are already known to inhibit Top1 as well as one or more of these DNA repair enzymes. 18 …”
Section: Introductionmentioning
confidence: 99%